Electroanalytical detection of pindolol: comparison of unmodified and reduced graphene oxide modified screen-printed graphite electrodes1. Issue 5 (7th March 2015) - Cumba, Loanda R.; Smith, Jamie P.; Brownson, Dale A. C.; Iniesta, Jesús; Metters, Jonathan P.; do Carmo, Devaney R.; Banks, Craig E.
<x xml:space="preserve">Abstract</x> We demonstrate, for the first time, that the electroanalytical quantification of pindolol is actually possible using bare (unmodified) screen-printed graphite electrodes (SPEs).